Treg: A Promising Immunotherapeutic Target in Oral Diseases - Zhang, Yujing; Guo, Jihua; Jia, Rong (Frontiers in Immunology, 2021)
With the pandemic of COVID-19, maintenance of oral health has increasingly become the main challenge of global health. Various common oral diseases, such as periodontitis and oral cancer, are closely associated with immune disorders in the oral mucosa. Regulatory T cells (Treg) are essential for maintaining self-tolerance and immunosuppression. During the process of periodontitis and apical periodontitis, two typical chronic immune-inflammatory diseases, Treg contributes to maintain host immune homeostasis and minimize tissue damage. In contrast, in the development of oral precancerous lesions and oral cancer, Treg is expected to be depleted or down-regulated to enhance the anti-tumor immune response. Therefore, a deeper understanding of the distribution, function, and regulatory mechanisms of Treg cells may provide a prospect for the immunotherapy of oral diseases. In this review, we summarize the distribution and multiple roles of Treg in different oral diseases and discuss the possible mechanisms involved in Treg cell regulation, hope to provide a reference for future Treg-targeted immunotherapy in the treatment of oral diseases.